The Description of Internal and External Factors of Fatigue at Sidoarjo Steel Smelting Company - Andy Juniar Syahfudin (Universitas Airlangga, 2019)
Introduction: Work fatigue or fatigue is a kind of body prevention from further damages. The fatigue experienced by a worker resulted in a decrease in work performance and lack of body endurance during the work. The workers of steel smelting companies are one of the examples of workers who potentially experience work fatigue. This research aims to ascertain both the internal and external factors of work fatigue experienced by the workers at Sidoarjo steel smelting company. Methods: This research was conducted at Sidoarjo steel smelting company in May 2018 with a population of 30 people. The internal factors in this research are the age, years of service, and nutritional status of the workers. Meanwhile, the external factors are the physical workload, work climate, and noise. This research is descriptive research with observation as the data collection method and is cross-sectional research design. The sample is calculated by applying the total population sampling technique. The data is presented descriptively in the form of frequency, percentage, and cross-tabulation among variables distributions. Result: It is revealed that the majority of the workers, as many as 17 people, undergo mild work fatigue (56.7%). The results of the cross-tabulation show that moderate and severe fatigues are mostly experienced by the workers with these criteria: younger, shorter years of service, obese, fair physical workload, and work climate and noise that exceed the Threshold Limit Value (TLV). Conclusion: It is affirmed that both the internal and external factors are related to work fatigue. Keywords: external factors, internal factors, steel smelting, work fatigue